PECULIARITIES OF MEDICAL AND PSYCHOLOGICAL REHABILITATION OF PARTICIPANTS OF MILITARY ACTIONS WITH POSTCONCUSSIONAL SYNDROME - Pronoza-Stebliuk, K. (Inter Collegas, 2020)
PECULIARITIES OF MEDICAL AND PSYCHOLOGICAL REHABILITATION OF PARTICIPANTS OF MILITARY ACTIONS WITH POSTCONCUSSIONAL SYNDROME. Pronoza-Steblyuk K. Subjects and metods. 48 families of veterans who had post-concussion syndrome, were directed for medical and psychological rehabilitation. At the beginning of the rehabilitation course, personal psychological problems (by anonymous survey and testing) were recognized  from 42 veterans and 44 veterans' wives. In 39 families were identified problems related to family relationships. The weekly courses included: the physical component of rehabilitation, psychological (psychotherapeutic) rehabilitation component and measures that are conditionally related to micro-social rehabilitation.Results. The applied of psychological assistance methods in combination with the physical and social components of the program led to an improvement in the personal psycho-emotional state of 96% of participants. Improvement of family understanding and psychological microclimate was noted by 100% of families. 60% of families expressed a desire to continue working with a psychologist. Based on the experience gained, recommendations have been made to improve mutual understanding in families. Conclusions. The use of these methods of intra-family psychological self-regulation will contribute to the normalization of relations, reduction of the clinical physical and mental effects of contusion, and improvement of the resocialization of veterans. Keywords: post-concussion syndrome, medical and psychological rehabilitation, family psychotherapy.